Case Study on the Role of Neuromotor Re-Education Methods in the Treatment of Charcot Marie-Tooth Disease - C.E. Stoica; G.S. Lupu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The isolated Charcot disease occurs in young people and has a motor onset, being a touch of motor cells, anywhere in the cerebrospinal axis. The paper is a case study of a subject diagnosed with Charcot Marie-Tooth disease. The physical therapy intervention aimed to apply elements of neuromotor re-education methods over a period of nine months. The results reveal that combining neuromotor re-education methods contributes to improving muscle elasticity and capsuloligamentous structures, thus preventing the formation of dysfunctional positions, and induces voluntary motor activity in the affected muscles, thus improving muscle imbalances specific to pathology.